2022
DOI: 10.1111/cid.13069
|View full text |Cite
|
Sign up to set email alerts
|

Monolithic zirconia single tooth implant‐supported restorations with CAD/CAM titanium abutments in the posterior region: A 1‐year prospective case series study

Abstract: To assess the clinical, radiographic, and patient-reported outcome measures, including the success of screw-retained monolithic zirconia implant-supported restorations with CAD/CAM titanium abutments in the posterior region during a 1-year follow-up.Methods: In a prospective case series, 50 molar sites in the posterior region of 46 patients with a minimum age of 18 years and sufficient bone volume and anatomical conditions for placing an implant (≥8 mm) and an anatomical restoration were included. Parallel-wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…After duplicate removal and title/abstract screening, 19 articles were selected for full-text analysis. Hence, 13 studies were excluded for the following reasons: the aim of the study was inconsistent with the aim of the systematic review [16,[26][27][28][29][30][31][32][33][34][35], overlapping data/same cohort [36] and the study design was inconsistent with the inclusion criteria [37]. The reasons for exclusion are available in Supplementary Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…After duplicate removal and title/abstract screening, 19 articles were selected for full-text analysis. Hence, 13 studies were excluded for the following reasons: the aim of the study was inconsistent with the aim of the systematic review [16,[26][27][28][29][30][31][32][33][34][35], overlapping data/same cohort [36] and the study design was inconsistent with the inclusion criteria [37]. The reasons for exclusion are available in Supplementary Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is possible to hypothesize that using permanent cement for implant-supported crowns may improve the long-term clinical outcomes. Screw-retained monolithic zirconia implant-supported restorations with CAD/CAM titanium abutments in the posterior region during a 1-year follow-up were studied by Donker et al and had survival rate of 100% for both implants and restorations with low technical and biological complications [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to consider that although there are too many studies conducted on such kinds of restorations, there is a lack of studies that evaluate monolithic zirconia with standardized USPHS parameters, exclusively the single-crown screwed-on implants are evaluated; thus, it was mandatory to compare our results to studies conducted on FDP or veneered zirconia. The studies that evaluated that specific population of prosthetic restoration have short-term follow-ups, with a maximum of three years [14,24,25]. In the first year of evaluation, each patient showed excellent parameters (41 on 41 alpha), which have to be considered better outcomes than the 1-year follow-up study of Pol et al, who reported bravo percentages of 21.4% and 3.6% regarding the marginal adaption and the opening of the anatomical morphology, respectively; however, they reported 100% survival, which is consistent with this study [26].…”
Section: Discussionmentioning
confidence: 99%